Bezier patch representation and its application to 3D facial modelling - Chong, Anthony Soon Keong. (2008)
This project presents a method of constructing a computer-based presentation of 3D graphical facial model using free form Bezier surface representation. A facial model is constructed by using 36 Bezier patches. Each individual patch will have its own defined control points.